ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIK DAN KEMAMPUAN DIRI SISWA SMP DI KABUPATEN BANDUNG BARAT - Putri Nurdwiandari (IKIP Siliwangi, 2018)
The ability to think critically is a process whereby one enables one to formulate and evaluate his own beliefs and opinions. The method used for the analysis of this research is Qualitative Descriptive Method that aims to analyze the results of students' work on critical thinking questions and self-tracking questionnaire students in SMPN 3 Batujajar West Bandung regency. The sample studied is 1 class of students who amounted to 39 students in class VIII-C SMPN 3 Batujajar in West Bandung regency. The test question used is critical mathematical thinking with 3 questions and non test self-efficacy on each student. The result of the analysis is the ability of mathematical critical thinking in junior high school in West Bandung regency based on the written description test is still quite low. This research is part of the thesis that will be examined by the author.